Sexual intercourse as a new option in the medical expulsive therapy of distal ureteral stones in males: A prospective, randomized, controlled study - Bayraktar, Zeki; Albayrak, Selami (Springer, 2017)
To investigate the effect of sexual intercourse on the spontaneous passage of distal ureteral stones 5-10 mm in size. A total of 190 male patients with distal ureteral stones were randomly divided into three groups. Patients in group 1 were administered tamsulosin 0.4 mg/day (n = 60). Patients in group 2 were asked to have sexual intercourse at least three times a week (n = 66). Patients in group 3 received standard medical therapy alone and acted as the controls (n = 64). The expulsion rate was controlled after 2 and 4 weeks. Differences between the groups were analyzed statistically by the Chi-square and Student's t test. p < 0.05 was considered as statistically significant. The mean ages of the patients in groups 1, 2, and 3 were 34.4 +/- 13.5 (18-60), 38.6 +/- 14.1 (18-63), and 36.92 +/- 12.4 (18-59) years, respectively (p > 0.05). The mean stone size was 7.09 +/- 1.4 mm in group 1, 7.01 +/- 1.4 mm in group 2, and 7.1 +/- 1.3 mm in group 3 (p > 0.05). Spontaneous passage rates in groups 1, 2, and 3 were 81.6, 81.8, and 51.5%, respectively, and it was significantly higher in group 1 (p = 0.0394) and group 2 (p = 0.0350). There was no significant difference between groups 1 and 2 (p = 0.9925). The analgesic needs in groups 1, 2, and 3 were found to be 1.3 +/- 0.4, 1.2 +/- 0.6, and 1.4 +/- 0.4 times, respectively, and were significantly lower in the sexual intercourse group than in the control group (p = 0.0276). Tamsulosin and sexual intercourse increase the spontaneous passage of distal ureteral stones 5-10 mm in size. At least three sexual intercourses per week seem to be at least as effective as tamsulosin. Sexual intercourse also reduces the need for analgesics in ureteric colic due to ureteral stones.
WOS: 000413117200007
PubMed ID: 28803386
Keywords: Medical Expulsive Therapy; Sexual Intercourse; Tamsulosin; Ureteral Stone